Harmonisasi Nilai Qur'an dan Kebijakan Pemerintah Tentang Rumah Ibadah: Telaah Pemikiran Buya Hamka - Fauzul Kabir (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the harmony between the values of the Qur’an and the Indonesian government’s policy on the establishment of houses of worship, with reference to Tafsir Al-Azhar by Buya Hamka. The research method used is qualitative descriptive, employing a library research approach. Data were collected from Qur’anic verses discussing houses of worship and from government regulations, particularly the Joint Regulation of the Minister of Religious Affairs and the Minister of Home Affairs Nos. 9 and 8 of 2006. The findings show that, according to Hamka, houses of worship serve both spiritual and social functions as places that strengthen human relationships with God and with others. The interpretation of Q.S. Ali ‘Imran [3]:96 emphasizes the value of piety in the establishment of places of worship, while Q.S. Al-Hajj [22]:40 highlights the importance of protecting all houses of worship as symbols of interreligious tolerance. These Qur’anic values are consistent with government policies that uphold the principles of justice, tolerance, and religious harmony. Thus, there exists a harmonization between divine revelation and state regulation in maintaining social harmony and religious freedom in Indonesia.